An Applied Study for the Restoration and Conservation of a Museum-Stored Colored Stone Coffin lid from the Late Period - Shaimaa Sayed Mohamed El-Sayed (Britain International for Academic Research (BIAR) Publisher, 2021)
The colored stone coffin lids are exposed to many different deterioration factors, whether in the burial or exposure environment. In the burial environment, these colored coffin lids are subjected to the pressure of soil sediments, which leads to their being crushed into parts, especially since the case study is made of limestone. In the soil, caused by the presence of ground water, which leads to the crystallization of salts and the growth of microorganisms. Also, false excavation of these colored stone coffins lids and their transfer from equilibrium in the burial environment to the exposure environment leads to exposing to other pressures and may lead to irreversible damage and loss of color, as the temperature difference in the exposure environment and burial environment will lead to fissures and cracks as well. Crystallization of salts in the case of high temperature, as well as the difference in relative humidity levels, will lead to the dissolution of the color-bonding material and the dissolution of the air pollution gases, which leads to the formation of acids that interact with the material of these stone coffins lids to form water-soluble compounds, which leads in the end to the loss and deterioration of them. The selected object of study is a colored stone coffin lid no. 1939, broken into several parts of limestone (about 13 parts), dated to the Late Period and saved in Atifyah museum store – Ministry of Tourism and Antiquities- Giza – Egypt, samples were taken from limestone, red and black pigments and examined by optical microscope, polarizing microscope and Scanning Electron Microscope (SEM) also analyzed by X-Ray Diffraction (XRD). The restoration processes are summarized in cleaning, consolidation, assembling and loss- compensation for the selected colored stone coffin lid.